Entwickeln sich wirtschaftswissenschaftliche Forschung und Politikberatung auseinander? - Justus Haucap; Michael Mödl; Christoph M. Schmidt; Nils aus dem Moore; Michael Themann; Wolfram F. Richter; Marcel Fratzscher; Gert G. Wagner; Werner Güth; Hartmut Kliemt; Willi Koll (Wirtschaftsdienst, 2013)
Ökonomen und Politiker beklagen sich gelegentlich übereinander. Die Ökonomen meinen, das politische Alltagsgeschäft berücksichtige die Erkenntnisse der Wissenschaft zu wenig und sei mit inkonsistenten Maßnahmen und suboptimalen Ergebnissen verbunden. Die Politiker sehen sich dagegen zum Teil mit realitätsfernen Empfehlungen konfrontiert. Die Bewertungsschemata für wissenschaftliche Exzellenz schaffen zudem Anreize für eher theoretisch ausgerichtete Forschung. Eine solch dramatische Diskrepanz zwischen Politikberatung und Forschung können die Autoren dieses Zeitgesprächs in der Regel nicht erkennen. – – Most German economists show strong patterns of professional specialisation. In their work, they either focus on basic research or on policy consultancy. The evidence provided by Haucap und Mödl has been used to question work incentives in academia. The suggestion to change work incentives, however, is not supported by Richter, who rather calls into question the German tradition of research funding. He argues that Germany should devote more competitive funding to research projects and less to institutions. Schmidt et al. explore the question the other way around: do policy consultants publish in top journals? They conclude that they do. Güth/Kliemt show how precarious and limited our (technologically useful) knowledge is. The discussion of alternative policies among economic experts should be used to tease out the controversial arguments to allow for better informed political judgements. Wagner/Fratzscher take a historical view, showing that when modern economic research (and economic research institutes) apply a more pluralistic paradigm than that which prevailed in Germany for a long period after the Second World War, economic research will automatically have a more significant impact on politics, since policy advisors will produce more varied advice with the potential for realisation. Koll also claims that policy advice must not be based on a single supply-side oriented mainstream point of view. By drawing lessons from the crisis, economics must identify a new mainstream providing reliable guidance and policy advice.
Keywords: A11; D78; 330; Wirtschaftspolitische Beratung; Theorie-Praxis-Verhältnis